Københavns Internationale Teater – en banebryder for scenekunst - Winkelhorn, Kathrine (Peripeti, 2022)
Copenhagen Interanational Theatre – breaking new grounds in performing arts Metropolis is organized by Copenhagen International Theater (KIT), which has been the primary driving force behind international, cross-disciplinary performing arts in Denmark since 1980 with festivals, seminars, workshops, and residencies. KIT has organized the legendary Fools Festivals, Dancin’ City, Images of Africa, Sommerscene, Dancin’ World, New Circus Festival, etc. as a major international platform in the Nordic countries. Presently KIT is working as an art-based metropolitan laboratory for the performative, site-specific and international art.